Olive groves around the lake. A ten-thousand-year history of a Cretan landscape (Greece) reveals the dominant role of humans in making this Mediterranean ecosystem. (1st September 2021) - Jouffroy-Bapicot, Isabelle; Pedrotta, Tiziana; Debret, Maxime; Field, Sophie; Sulpizio, Roberto; Zanchetta, Giovanni; Sabatier, Pierre; Roberts, Neil; Tinner, Willy; Walsh, Kevin; Vannière, Boris
Abstract: The reconstruction of millennial-scale interactions between ecosystems and societies can provide unique and valuable references for understanding the creation of cultural landscapes and help elucidate their value, weaknesses and legacies. Among the most emblematic forms of Mediterranean land use, olive groves and pastoralism have occupied a prominent place. Therefore, it is vital to know when, how, and with what ecological consequences these practices were established and developed. Located in the southern part of the Aegean Sea, Crete is the largest island of Greece. The island is characterised by a long human history of land use, but our understanding of past environmental changes for the entire Holocene is fragmentary. This paper presents a new investigation of Lake Kournas in Crete, where recent coring provided a 15-m sequence covering ten millennia of land cover and land-use history. The study of this new core involves the analysis of the sediment dynamics, flood deposits, pollen, diatoms, fungal and algal remains, and microcharcoals. Results show that ecosystem development near Lake Kournas was not a linear process. They reveal linkages and feedbacks between vegetation, biodiversity, fire, human impact, erosion, and climate change. A possible human occupation and agro-pastoral activities around the lake may have been detected as early as 9500 cal BP, perhaps in a transitional phase between the Mesolithic and the Neolithic. At 8500 cal BP, climatic conditions may have promoted the expansion of the evergreen oak woodland. However, human impact was probably the most important driver of ecosystem change with the establishment of an agro-system after 8000 years ago. Thereafter, the trajectory of Kournas' lake and catchment ecosystems from the Mid to Late Holocene follow the rhythm of land-use change. Among the traditional Mediterranean land uses, olive cultivation locally played a major role in the socio-ecosystem interactions, providing economic benefits but also destabilising soils. During the last six millennia, three main phases of olive cultivation occurred during the Final Neolithic-Minoan period, the Hellenistic-Roman-Byzantine (HRB) period and Modern times. Along with the changing land use under the successive political and economic influences rules, the resilience capacities of vegetation permitted it to shift back to higher biodiversity again after decreasing phases. Forest vegetation was always able to recover until the onset of the Venetian period (13th century), when woodlands were dramatically reduced. Only during the past century has forest vegetation slightly recovered, while the flood regime had already been altered during previous centuries. During the past 100 years, biodiversity markedly declined, probably in response to the industrialization of agriculture. Highlights: The Lake Kournas core study includes sediment, pollen, NPP, diatom and microcharcoal analyses. The results reveal almost ten millennia of interactions between climate, human activities, erosion, vegetation and fire. Climate may have been involved in the first shift around 8500 cal BP that promoted expansion of evergreen oak woodland. From the Mid to the Late Holocene, the ecosystem trajectory near the lake rather follows the rhythm of land use changes. Among the traditional Mediterranean land uses, olive cultivation locally played a major role.